Statistical Software Applications and Statistical Methods Used In Community Medicine and Public Health Research Studies - Joshi, Krishna P; Jamadar, Deepak C (National Journal of Community Medicine, 2021)
Background: The utilization of software in statistical methods and tools has increased very much in last two decades. The easily availability of statistical application software on internet, made easy to analyse, interpretation and conclude the study variables. Aim and Objectives: To know the statistical software applications and various statistical methods used in the community medicine and public health research studies. Materials & Methods: A cross sectional retrospective study, We had included online community medicine and public health journals of four years (2017 to 2020).By cluster sampling method were used and each cluster includes articles of four different year, 400 randomly selected research articles were downloaded & reviewed. The data was analysed by using SPSS version 23. Results: 400 articles were reviewed. 317 (79.25%) were used Ms-Excel software followed by 261 (65.25%) descriptive statistics and 145(36.25%) SPSS and 143 (35.75%) applied cross sectional study design. 91 (22.75%) applied chi-square test, 77(19.25%) applied ANOVA test. 59(14.75%) t-tests. Only 41(10.25%) articles were reported with confidence intervals. Conclusion: The current study reveals, Microsoft excels, and SPSS and R-programming were more frequently using software in the community medicine and public health, whereas descriptive statistics, chi-square tests, t-tests and non-parametric tests were commonly using statistical methods.